Diphenyl pyridine intervention improves S. aureus-induced pneumonia by globally regulating transcriptome profile - Duan, Wei; Zhu, Qingfeng; Ci, Hai; Zhang, Jingang; Tian, Zhiwei; Li, Wanyu; Yang, Zhengfu (Frontiers in Genetics, 2025)
BackgroundPneumonia, induced by various bacteria or viruses, is a globally prevalent inflammatory disease that threatens the life of millions of people. Staphylococcus aureus (S. aureus) is a major pathogen of pneumonia and can be inhibited by Diphenyl pyrimidine (DP), while the underlying mechanisms are largely unknown.MethodsIn this study, we conducted the S. aureus-induced rat pneumonia model and then performed DP treatment to inhibit the injury. Meanwhile, whole transcriptome sequencing (RNA-seq) experiment was performed to identify the dysregulated genes with expression and alternative splicing changes, as well as their enriched functions. Hub genes and immune cell proportion changes by DP were also identified to explore the underlying mechanism.ResultsWe identified 2,225 up and 1,257 down DEGs between DP and SA samples, and found they were significantly enriched in immune and inflammatory response pathways, as well as angiogenesis and apoptosis pathways. At the same time, DP treatment also significantly altered the alternative splicing profile, including 3898 AS genes and 416 co-regulated genes with DEGs. Functional analysis of co-regulated genes demonstrated they were enriched in immune response, signal transduction, and apoptosis regulation pathways. Finally, we identified ten hub genes by protein-protein network analysis from DEGs, including CCNA2, TOP2A, CDK1, ESPL1, KIF2C, PBK, UHRF1, RACGAP1, PCLAF, and RAD51 that were totally repressed by DP treatment.ConclusionIn summary, our study demonstrated that DP treatment can profoundly modulate the immune and inflammatory response by regulating the transcriptome profile of peripheral blood monocytes (PBMCs). The identified hub genes by DP treatment are potential therapeutic targets for S. aureus-induced pneumonia in future.